Strategy and tactics of emergency treatment of atrial fibrillation: a modern approach to the problem - Yu. A Bunin (КардиоСоматика, 2015)
Atrial fibrillation (AF) is the most common tachyarrhythmiac detection which in the general population is 1.0-2.0%. It is the cause of 20% of all strokes, associated with an increase in mortality and the risk of chronic heart failure. Paroxysms are often accompanied by deterioration of the patient's hemodynamic instability, requiring emergency medical care.The article presents a modern view on strategy and tactics cupping AF indication for pharmacological cardioversion and cardioversion. As the basis of the material made by the international guidelines on the management of patients with atrial fibrillation, as well as data from a number of modern-controlled studies and own clinical experience treating arrhythmias.However, the article dealt with some of the controversial issues of emergency treatment of AF and expresses the point of view of the author on a number of studies in this area arrhythmology.